Guest Editors' Introduction. Issue 2 (2nd April 2016) - Czakon, Wojciech; Dagnino, Giovanni Battista; Le Roy, Frédéric
Abstract: We adopt the view of coopetition as a research program, way more than just a stream of literature. A growing community of researchers investigates coopetition's nature, process, impact on strategies and subsequent performance. This special issue marks a step in the research program development. By identifying the four levels of analysis i.e. macro, meso, micro and microfundamental we frame the questions that guide coopetition theorizing. Three papers have been selected to illuminate current progress, focused on value creation. First, a study on common value creation offers insights into how firms are able to generate benefits available to coopetitors. Secondly, conceptual insights into the coopetition strategy process are developed. Thirdly, an in-depth study of value creation in coopetition settings offers a multilevel typology of seven coopetition forms.